An extensive ameloblastic fibroma involving bilateral side of the mandible in a teenager - Ghazali, Ahmad Badruddin; Arayasantiparb, Raweewan; Juengsomjit, Rachai (2021)
Introduction Ameloblastic fibroma is a rare benign odontogenic tumor comprising of both epithelial and mesenchymal cells. It is commonly diagnosed in the first two decades of life and has slight male predilection. Case We report a case of ameloblastic fibroma in a 15-year-old girl with complaint of extensive swelling of mandibular region for three years. Large field of view cone beam computed tomography revealed large multilocular radiolucency in both sides of the jaw from 37 to 47 area causing impaction, displacement, transposition and root resorption. A presumptive preoperative diagnosis of ameloblastoma was made. Incisional biopsy showed odontogenic epithelial islands and mesenchymal connective tissue cells leading to diagnosis of ameloblastic fibroma. The treatment done was partial mandibulectomy and reconstruction with iliac crest bone graft under general anesthesia. The 14-month postoperative follow-up showed no recurrence for this patient. Discussion The case is interesting because the patient is a young female teenager but presented with large tumor crossing the midline of the mandible, requiring aggressive treatment. Long term follow up is highly recommended to detect any recurrence and possible transformation into malignancy.